Intensification of the polycrisis and the rise of a technooligarchic ideology in the USA - Vrečko Ilc, Blaž (Teorija in praksa, 2025)
The article analyses the techno-oligarchic ideology in the USA during the 2nd Trump Administration and the implications it holds for tackling the climate/ecological crisis. It argues that this ideology is a novel, far-right political ideology of the US techno-oligarchy whose rise was predicated on intensification of the polycrisis. Its central purpose is to expand the techno-oligarchy’s influence, power and wealth, and squash opposition to its dominance and any visions/policies that critically interrogate the existing ecologically unsustainable capitalist model of growth and technological development. By analysing its central characteristics, its re-imagining of the state and political institutions via the introduction of AI, and in the context of the Israeli genocide of Palestinians, the article shows that its novel nature stems from the centrality of technological development and technology(ies) in its oligarchic, anti-democratic, repressive, neo-imperial, eugenic, hyper-capitalist, extractive and destructive vision of society.
Keywords: AI; artificial intelligence; far-right political ideology; genocid; Ideologija; Krize; Oligarhija; polikriza; politična ideologija; polycrisis; techno-oligarchy; tehnologija; tehnooligarhija; the state; umetna inteligenca